KODE NARASI DALAM NOVEL ‘KING SOLOMON’S MINES’ - Heri Yusup (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
This paper discusses the narrative technique of ‘King Solomon’s Mines’, an adventure story novel written by Rider Haggard. This thesis aims to show that technique of the narration is the narrator’s effort to attract curiosity and to bring out imaginative fantasy. The technique is analyzed through the textual signifiers used in describing the characters and presenting the details. The method of analysis is based on Roland Barthes’s Textual Analysis that reveals what is known as narrative code. The research finding shows that the narrative codes which the novel has serve as ‘the appetizer’ to attract reader’s curiosity and as facilitator to bring out the imaginative fantasy